2015
DOI: 10.1111/jopy.12147
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional‐Compounding Effects of Rumination and Negative Emotion in Predicting Impulsive Behavior: Implications for Emotional Cascades

Abstract: Influenced by chaos theory, the emotional cascade model proposes that rumination and negative emotion may promote each other in a self-amplifying cycle that increases over time. Accordingly, exponential-compounding effects may better describe the relationship between rumination and negative emotion when they occur in impulsive persons, and predict impulsive behavior. Forty-seven community and undergraduate participants who reported frequent engagement in impulsive behaviors monitored their ruminative thoughts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 46 publications
8
51
0
1
Order By: Relevance
“…In particular, there has been a growing body of research examining rumination in the context of anxiety and substance use, and most recently in EDs (Aldao et al, 2010). Similar to studies of rumination in depression, evidence suggests that rumination has an amplifying effect on negative emotions and maladaptive behaviors in other diagnostic groups (Caselli et al, 2010; Nolen-Hoeksema, Stice, Wade, & Bohon, 2007; Selby, Kranzler, Panza, & Fehling, 2016). This was supported by a previous meta-analysis that examined associations between emotion regulation strategies and four types of psychopathology (i.e., depression, anxiety, substance use disorders, and EDs), which found the association between psychopathology and rumination was strongest compared to other emotion regulation strategies (Aldao et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…In particular, there has been a growing body of research examining rumination in the context of anxiety and substance use, and most recently in EDs (Aldao et al, 2010). Similar to studies of rumination in depression, evidence suggests that rumination has an amplifying effect on negative emotions and maladaptive behaviors in other diagnostic groups (Caselli et al, 2010; Nolen-Hoeksema, Stice, Wade, & Bohon, 2007; Selby, Kranzler, Panza, & Fehling, 2016). This was supported by a previous meta-analysis that examined associations between emotion regulation strategies and four types of psychopathology (i.e., depression, anxiety, substance use disorders, and EDs), which found the association between psychopathology and rumination was strongest compared to other emotion regulation strategies (Aldao et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…As the Emotional Cascade Model has a feedback loop in which aversive emotions lead consequently to dysregulated behaviour which then, temporally, reduces the experience of negative emotion, findings from a cross‐sectional study may be interpreted with caution and they should be replicated in further studies using longitudinal methods. However, other studies using experience sampling research have demonstrated that both rumination and negative emotion predict subsequently higher levels of each other, as well as subsequent engagement in dyscontrolled behaviours (Selby, Kranzler, et al, in press). Second, the study did not explore episodes in which patients have had severe aggressive behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As the intensity of the emotion rises, the individual finds that it is more and more difficult to divert attention away from emotional experience, and as a result, he or she pays more attention to emotional stimuli, intensifying the intensity of rumination. This interplay between rumination and negative emotion results in a positive feedback loop between the two that generates a progressively worsening aversive emotional and cognitive experience that is difficult to terminate (Selby & Joiner, ; Selby, Kranzler, Fehling, & Panza, in press). Thus, the end result of an emotional cascade is an extremely high, extremely aversive, state of negative affect that is self‐perpetuating, and patients with BPD have trouble regulating.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, several studies have employed EMA to assess different forms of momentary RNT [14,[18][19][20][21]. However, the majority of these studies have predominantly focused on one specific content of RNT only (e.g., either worry, i.e.…”
Section: Introductionmentioning
confidence: 99%